The effects of air pollution on asthma hospital admissions in Adelaide, South Australia, 2003–2013: time‐series and case–crossover analyses. Issue 11 (20th September 2016) - Chen, K.; Glonek, G.; Hansen, A.; Williams, S.; Tuke, J.; Salter, A.; Bi, P.
Summary: Background: Air pollution can have adverse health effects on asthma sufferers, but the effects vary with geographic, environmental and population characteristics. There has been no long time‐series study in Australia to quantify the effects of environmental factors including pollen on asthma hospitalizations. Objectives: This study aimed to assess the seasonal impact of air pollutants and aeroallergens on the risk of asthma hospital admissions for adults and children in Adelaide, South Australia. Methods: Data on hospital admissions, meteorological conditions, air quality and pollen counts for the period 2003–2013 were sourced. Time‐series analysis and case–crossover analysis were used to assess the short‐term effects of air pollution on asthma hospitalizations. For the time‐series analysis, generalized log‐linear quasi‐Poisson and negative binomial regressions were used to assess the relationships, controlling for seasonality and long‐term trends using flexible spline functions. For the case–crossover analysis, conditional logistic regression was used to compute the effect estimates with time‐stratified referent selection strategies. Results: A total of 36, 024 asthma admissions were considered. Findings indicated that the largest effects on asthma admissions related to PM2.5, NO2, PM10 and pollen were found in the cool season for children (0–17 years), with the 5‐day cumulative effects of 30.2% (95% CI: 13.4–49.6%), 12.5% (95% CI: 6.6–18.7%), 8.3% (95% CI: 2.5–14.4%) and 4.2% (95% CI: 2.2–6.1%) increases in risk of asthma hospital admissions per 10 unit increments, respectively. The largest effect for ozone was found in the warm season for children with the 5‐day cumulative effect of an 11.7% (95% CI: 5.8–17.9%) increase in risk of asthma hospital admissions per 10 ppb increment in ozone level. Conclusion: Findings suggest that children are more vulnerable and the associations between exposure to air pollutants and asthma hospitalizations tended to be stronger in the cool season compared to the warm season, with the exception of ozone. This study has important public health implications and provides valuable evidence for the development of policies for asthma management.